FGIN-1-27 Inhibits Melanogenesis by Regulating Protein Kinase A/cAMP-Responsive Element-Binding, Protein Kinase C-β, and Mitogen-Activated Protein Kinase Pathways - Lv, Jinpeng; Jiang, Songzhou; Yang, Ying; Zhang, Ximei; Gao, Rongyin; Cao, Yan; Song, Guoqiang (Frontiers in Pharmacology, 2020)
FGIN-1-27 is a synthetic mitochondrial diazepam binding inhibitor receptor (MDR) agonist that has demonstrated pro-apoptotic, anti-anxiety, and steroidogenic activity in various studies. Here we report, for the first time, the anti-melanogenic efficacy of FGIN-1-27 in vitro and in vivo. FGIN-1-27 significantly inhibited basal and α-melanocyte-stimulating hormone (α-MSH)-, 1-Oleoyl-2-acetyl-sn-glycerol (OAG)- and Endothelin-1 (ET-1) -induced melanogenesis without cellular toxicity. Mushroom tyrosinase activity assay showed that FGIN-1-27 did not directly inhibit tyrosinase activity, which suggested that FGIN-1-27 was not a direct inhibitor of tyrosinase. Although it was not capable of modulating the catalytic activity of mushroom tyrosinase in vitro, FGIN-1-27 downregulated the expression levels of key proteins that function in melanogenesis. FGIN-1-27 played these functions mainly by suppressing the PKA/CREB, PKC-β, and MAPK pathways. Once inactivated, it decreased the expression of MITF, tyrosinase, TRP-1, TRP-2, and inhibited the tyrosinase activity, finally inhibiting melanogenesis. During in vivo experiments, FGIN-1-27 inhibited the body pigmentation of zebrafish and reduced UVB-induced hyperpigmentation in guinea pig skin, but not a reduction of numbers of melanocytes. Our findings indicated that FGIN-1-27 exhibited no cytotoxicity and inhibited melanogenesis in both in vitro and in vivo models. It may prove quite useful as a safer skin-whitening agent.